(untitled) (Bangladesh Journal of Agricultural Research, 2011)
The concept of yield gaps originated from the studies conducted by IRRI in the seventies. The yield gap discussed in this paper is the difference between the potential farm yield and the actual average farm yield. In Bangladesh, yield gaps exist in different crops ranging up to 60%. According to the recent study conducted by BRRI, the yield gap in rice was estimated at 1.74 t/ha. The existence of yield gaps was as well observed in rice, mustard, wheat and cotton in India. In India, yield gap varied from 15.5 to 60% with the national average gap of 52.3% in irrigated ecosystem. The yield gaps are mainly caused by biological, socio-economic, climate and institutional/policy related factors. Different strategies, such as integrated crop management (1CM) practices, timely supply of inputs including credit to farmers, research and extension collaboration to transfer the new technologies have been discussed as strategies to minimize yield gaps. Suggestions have been made to make credit available to resource-poor small farmers to buy necessary inputs. Reducing transaction cost, simplifying lending procedures and strengthening monitoring mechanism of the current credit system are, however, essential to enable the farmers to avail the credit facility. Efforts should be made to update farmers’ knowledge on the causes of yield gaps in crops and measures to narrow the gaps through training, demonstrations, field visits and monitoring by extension agencies to achieve high yield. The government should realize that yield gaps exist in different crops of Bangladesh and therefore, explore the scope to increase production as well as productivity of crops by narrowing the yield gap and thereby ensure food security. Keywords: Yield gaps; strategies; crops of Bangladesh. DOI: http://dx.doi.org/10.3329/bjar.v36i3.9274 BJAR 2011; 36(3): 469-476